Development of Bacillus thuringiensis-based liquid and paste formulations for controlling invasive pest species Spodoptera frugiperda J. E. Smith - Djunaedy, Achmad; Khoiri, Syaiful; Azari, Dheananda Fyora Hermansyah; Syamsiyah, Zahratus; Pawana, Gita; Megasari, Dita; Giyanto, Giyanto (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2024)
Spodoptera frugiperda J.E. Smith (Spodoptera: Noctuidae) is an invasive pests of maize that has been reported around the world. Control efforts using biological agents continue to be developed, including the use of entomopathogen bacteria such as Bacillus thuringiensis. To boost the efficacy and efficiency of biological control, formulations are required. The objective of this study was to develop biopesticide formulations and evaluate their efficacy. The research was carried out by formulating B. thuringiensis strain BtJ2 (1010 cfu mL -1) in liquid and paste formulations. The effectiveness of the formulations was evaluated using the feed dipping method. The results showed that paste formulations at a concentration of 10% caused 100% mortality, whereas the liquid formulation resulted in 85% mortality. The LC90 for the paste formulation was 6.66%, while the LC90 for the liquid formulation was 12.90%. Both the liquid and paste formulations had similar effects on mortality and viability. Based on the LC90 and LT90, the paste formulation was more efficient and faster in killing S. frugiperda than the liquid formulation. The results of this study provide recommendations that B. thuringiensis as a bioinsecticide is better formulated in a paste than in a liquid form.